Rupture of a large aneurysm of common hepatic artery - case report - Opatrný, V; Houdek, K; Moláček, J; Čertík, B; Šulc, R; Třeška, V (Rozhledy v chirurgii, 2022)
Visceral artery aneurysms are rare findings in the practice of vascular surgeons. Their inaccessibility to physical examination, asymptomatic nature in many cases, but also an inherent risk of rupture that can be life threatening, make them a complex diagnostic and therapeutic problem. By presenting a case report of a ruptured common hepatic artery aneurysm the authors summarize basic characteristics of these aneurysms, as well as diagnostic and treatment options.
Keywords: rupture; Tomography, X-Ray Computed; Hepatic Artery; Humans; počítačová rentgenová tomografie; visceral arteries; lidé; Aneurysm, Ruptured; aneurysm; arteria hepatica; prasklé aneurysma